(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To investigate the prevalence of and risk factors for diabetic retinopathy in areas differing in access to endocrinologic care. Materials and Methods: The study was conducted in the Ganja-Gazakh economic region, whose administrative units differ from each other with respect to access to endocrinologic care and prevalence of type 1 diabetes mellitus and type 2 diabetes mellitus. In order to determine actual prevalence of diabetic retinopathy across the region, 479 diabetics underwent a routine examination. Results: Diabetic retinopathy was found in 28.8±2.1% (95% CI, 24.6%–33.0%) of patients with diabetes mellitus. It was found substantially less frequently in diabetics from the city of Ganja than in those from rural settlements with no access to endocrinologic care at the local level. Non-proliferative diabetic retinopathy was the most common form of the disease (50.0±4.3%), followed by pre-proliferative and proliferative forms (34.1% and 15.9%, respectively). Pre-proliferative and proliferative forms were 2.8 times and 2.2 times, respectively, more common in the group of patients with no access to endocrinology service at the area of patient residence. Conclusion: The difference in local access to endocrinologic care among administrative units of the region is associated with the difference in risk for and late detection of diabetic retinopathy. Gender, type of diabetes, presence of complications, duration of diabetes mellitus, and treatment regimens are important risk factors for the development of diabetic retinopathy.